Double-Ring Vaccination As Acceleration Tools of Measles Vaccination Coverage in Papua - Isak Jurun Hans Tukayo; Blestina Maryorita; Jems Kifen Rogert Maay; Sukatemin Sukatemin (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2023)
Seven districts in Papua experienced an increase in measles cases during the Covid pandemic, namely Nabire, Paniai, Mimika, Puncak, Dogiyai, Intan Jaya, and Deiyai. So far, there is no policy that is truly effective in efforts to increase the coverage of measles immunization in pandemic areas such as Papua. The objectives to develop a policy brief that can provide recommendations for increasing the coverage of measles immunization in pandemic areas. This study used a quantitative method with a descriptive design. The instrument was a questionnaire distributed online, in Papua Province and held in July-August 2023. The population was 120 health workers. The inclusion criteria were nurses who are directly involved in the management of measles in Papua. The exclusion criteria were health workers in Papua or outside Papua and those who do not treat measles. The dependent variable was measles. The independent variable was immunization coverage. The secondary data were taken from official government documents or WHO and the Indonesian Ministry of Health and reputable journals. Data processing was carried out univariately and analyzed descriptively. The results showed the majority of respondents were involved in the measles program (n=62 or 54.3%), witnessed an increase in measles cases during the pandemic (n=87 or 76.3%), and considered the measles management program to be ineffective (n=69 or 59.3%). The most influential factors in the decrease in the measles vaccination rate were a mixture of fear, lack of knowledge, and culture (n: 59 or 52%) The majority think it is necessary to make changes to the measles program policy (n: 82 or 72%) The aspect that was most needed in policy changes was a combination of mechanisms, human resource facilities, and procedures (n=33 or 29%). This study recommends a policy brief on double-ring vaccination, namely the administration of measles vaccination in two areas surrounding the area affected by the measles outbreak.